Opinions of Prison Managers on Juvenile Prisons (Archives of Criminology, 2008)
This paper presents the findings of research on the perception of the French concept of juvenile prisons by managers of Polish penitentiary facilities in the context of potentially creating similar facilities in Poland. The author describes the French model of juvenile prisons based on conclusions from an analysis of French legal texts and official documents concerning ways of preventing juvenile crime. The article also shows a comparative analysis of juvenile delinquency in France and Poland based on numerical data presented in tables. Stępniak indicates that despite the increasing number of crimes committed by minors, the rate in Poland is lower than in France. Further, the text contains information on the reform of the criminal law and the provisions on the punishment of minors in France. Moreover, he describes the so-called ‘13 200 programme’, aimed at improving the conditions of imprisonment for minors – who were previously incarcerated in adult prisons – and implementing new educational methods. The final section of the article contains the results of a survey conducted among the Polish penitentiary personnel – students of the Penitentiary Studies at the Adam Mickiewicz University in Poznań– on the French model of juvenile prisons and whether it should be introduced in Poland. The author outlines the methods of the survey and characterises the respondents. The paper contains an analysis of the findings, taking into account the respondents’ opinions on the benefits of creating juvenile prisons, the effects of employing people from outside the prison service in prisons, and the introduction of prison guards in correctional institutions. Based on the results, the author expresses his lack of support for the concept of creating juvenile prisons due to the current organisation of Polish penitentiary facilities. Moreover, the respondents did not perceive major benefits from the creation of special prisons for juveniles. On the other hand, the proposal to partially incorporate correctional facilities into the penitentiary system received strong support.